2022
DOI: 10.1002/acr.24786
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Prevalence, and Mortality of Dermatomyositis: A Population‐Based Cohort Study

Abstract: Objective. We aimed to determine the population-based incidence, prevalence, and mortality of dermatomyositis (DM) using European Alliance of Associations for Rheumatology (EULAR)/American College of Rheumatology (ACR) criteria.Methods. This population-based cohort study included incident DM from January 1, 1995 to December 31, 2019. We manually reviewed all individuals with at least 1 code for DM or polymyositis to determine if they met EULAR/ ACR criteria, subspecialty physician diagnosis, and/or Bohan and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Dermatomyositis is a rare disease with an incidence of 1 to 15 per million [ 1 ]. Apart from muscle and skin, the disease can also affect other organs, such as lungs, heart, and blood vessels with varying clinical outcomes, depending on the specific antibody [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dermatomyositis is a rare disease with an incidence of 1 to 15 per million [ 1 ]. Apart from muscle and skin, the disease can also affect other organs, such as lungs, heart, and blood vessels with varying clinical outcomes, depending on the specific antibody [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the few available studies, most demonstrate a stable incidence of DM, with the exception of a small cohort study from Olmsted County, Minnesota . A more recent study from Olmsted County demonstrated no change in incidence from 2009 to 2017 compared with the period from 1995 to 2007 . There are more studies evaluating idiopathic inflammatory myopathies as a whole or evaluating polymyositis plus DM .…”
Section: Discussionmentioning
confidence: 99%
“…The use of ICD-9 or ICD-10 coding to identify patients with DM has its limitations. Kronzer et al reported a positive predictive value of 49% for 2 DM ICD-9 or ICD-10 codes when using EULAR/ACR (European Alliance of Associations for Rheumatology/American College of Rheumatology) 2017 diagnostic criteria. This suggests that ICD-9 and ICD-10 coding alone is not precise in identifying DM cases.…”
Section: Discussionmentioning
confidence: 99%
“…This group also includes polymyositis, inclusion body myositis, and immune‐mediated necrotizing myopathy 1,2 . DM is characterized by proximal muscle weakness, skin involvement, and an increased risk of developing interstitial lung disease 3,4 . Gottron's papules, skin ulceration, mechanic hands, and heliotrope eruption are characteristic skin lesions in patients with DM 5,6 .…”
Section: Introductionmentioning
confidence: 99%